Preparation and application of a novel durable hydrophilic finishing agent for polyamide fabric. Issue 9 (2nd September 2019) - Sun, Yufa; Zhou, Xiangdong
Abstract: A novel polyamide–polyether block copolymer (PPBC) was successfully prepared with polypropylene glycol (PPG-1000), succinic anhydride (SA), adipic acid (AA) and hexamethylenediamine (HAD) via condensation polymerization. The synthesized PPBC was characterized by Fourier transform infrared spectroscopy (FT-IR), gel permeation chromatography (GPC) and thermogravimetric analysis (TG). Afterwards, PPBC as hydrophilic finishing agent was treated onto polyamide fabric by a pad-dry-cure method. Scanning electron microscope (SEM) showed that PPBC had been successfully finished on the surface of polyamide fiber. X-ray diffraction (XRD) and differential scanning calorimetry (DSC) results suggested that the crystallinity of polyamide fiber finished by PPBC decreased, and the reason might be that PPBC interacted with the crystalline region of polyamide fiber. The hydrophilicity of polyamide fabric finished by PPBC had good washing fastness may illustrate the reason further. Furthermore, hydrophilicity of polyamide fabric was evaluated by wetting time (WT) and water contact angle (WCA). The experimental results showed that the WT and WCA values of polyamide fabric finished by PPBC were significantly improved from 60.7 s and 115° to 5.3 s and 68°, respectively.